The person as a research subject: approaches to his study - Lolas-Stepke, Fernando (2005)
After conceptualizing biomedical and psychosocial research as a social practice involving numerous actors, this article concentrates on subjects (or participants) in experiments, observations, studies and pharmacological trials, emphasizing the scarce attention which their attribvutes have received despite the implicit and explicit recognition of their importance in knowledge production. The need to specify traits and characters of the “volunteer” and their decisive influence on psychological and social studies is emphasized.